Use of antenatal care services in Kassala, eastern Sudan - Abbaker Ameer O; Osman Mohammed M; Ali Abdel Aziem A; Adam Ishag (BMC, 2010)
Abstract Background Antenatal care is named as one of the four pillars initiatives of the Safe Motherhood Initiative. While many of routine antenatal care procedure have little effect on maternal mortality and morbidity, some of these have been ascertained as beneficial. The aim of this study was to investigate coverage of antenatal care and identify factors associated with inadequacy of antenatal care in Kassala, eastern Sudan. Methods A cross-sectional community-based study was carried out in Kassala, eastern Sudan during September-October 2009. Household surveys were conducted. Structured questionnaires were used to gather data from women who had been pregnant within the last year, or pregnant more than 14 weeks. Results Out of 900 women investigated for antenatal care coverage, 811(90%) women had at least one visit. Only 11% of the investigated women had ≥ four antenatal visits, while 10.0% had not attended at all. Out of 811 women who attended at least one visit, 483 (59.6%), 303 (37.4%) and 25 (3.1%) women attended antenatal care in the first, second and third trimester, respectively. In logistic regression analyses, while maternal age and residence were not associated with inadequacy of antenatal care (<2 visits), high parity (OR = 2.0, CI = 1.1-3.5; P = 0.01) and husband education ≤ secondary level (OR = 2.4, CI = 1.3-4.2; P = 0.002) were associated with inadequacy of antenatal care. Conclusions Antenatal care showed a low coverage in Kassala, eastern Sudan. This low coverage was associated with high parity and low husband education.